Experimental and numerical study on the transport of droplet aerosols generated by occupants in a fever clinic. (January 2021) - Zhou, Yu; Ji, Shen
Abstract: The outbreak of the corona virus disease 2019 (COVID-19) infection has spread to a large number of countries worldwide. The early diagnosis of COVID-19 is complicated by its strong transmission characteristics and no obvious symptoms in the incubation period. Due to the relatively sealed indoor environment and the existing ventilation system, the patients and doctors in the fever clinics of the major hospitals are faced with a huge risk of infection. This study aims to investigate the transport of droplet aerosols generated by both doctors and patients to seek measures to reduce the risk of infection. Taking a typical fever clinic as an object of study, two links in the actual diagnosis and treatment process are selected in this manuscript for investigation by experimental and numerical methods. The effects of different cases of coughing and talking, as well as different contact distances, on the inhalation rate of human droplet aerosols are studied. The purification capacity of the ventilation is evaluated by the analysis results of the particle diffusion track and regional concentration of the entire indoor area and breathing zones. The results show that purification of the same number of droplet aerosols and purification by ventilation work better for coughing than for talking. The best ventilation performance appeared for the case of a patient sitting and coughing (PSC), while the case of a patient lying and talking (PLT) was the worst. Corresponding measures are suggested to improve the air purification effect and reduce the risk of cross infection. Highlights: The transport of droplet aerosols was investigated in a typical fever clinic. Twelve different cases were studied to analyses particle diffusion track and regional concentration. Both experiment and numerical method were performed. The purification capacity of the ventilation was evaluated in the entire indoor area and breathing zones. Expected risk of infection from both patients and doctors.